Seasonal variation in nitrogen fixation and effects of climate change in a subarctic heath - Lett, Signe; Michelsen, Anders (Plant and soil, 2014)
Background and aims Nitrogen fixation associated with cryptogams is potentially very important in arctic and subarctic terrestrial ecosystems, as it is a source of new nitrogen (N) into these highly N limited systems. Moss-, lichen-and legume-associated N₂ fixation was studied with high frequency (every second week) during spring, summer, autumn and early winter to uncover the seasonal variation in input of atmospheric N₂ to a subarctic heath with an altered climate. Methods We estimated N₂ fixation from ethylene production by acetylene reduction assay in situ in a field experiment with the treatments: long-vs. short-term summer warming using plastic tents and litter addition (simulating expansion of the birch forest). Results N₂ fixation activity was measured from late April to mid November and 33 % of all N₂ was fixed outside the vascular plant growing season (Jun-Aug). This substantial amount underlines the importance of N₂ fixation in the cold period. Wanning increased N₂ fixation two-to fivefold during late spring. However, longterm summer warming tended to decrease N₂ fixation outside the treatment (tents present) period. Litter alone did not alter N₂ fixation but in combination with warming N₂ fixation increased, probably because N₂ fixation became phosphorus limited under higher temperatures, which was alleviated by the P supply from the litter. Conclusion In subarctic heath, the current N₂ fixation period extends far beyond the vascular plant growing season. Climate warming and indirect effects such as vegetation changes affect the process of N₂ fixation in different directions and thereby complicate predictions of future N cycling.